2019
DOI: 10.1021/acsomega.9b00016
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of α-Acids in Fresh Hops by Reverse-Phase High-Performance Liquid Chromatography

Abstract: This publication describes a method for the quantification by high-performance liquid chromatography (HPLC) of resinous compounds known as α-acids found in freshly harvested, unprocessed hops. This method provides consistent, efficient, and accurate results as well as the theories and rationale involved in HPLC method development. A system of quality checks was utilized as well as the validation of numerous developmental variables. By starting with a theoretical approach in preparation, extraction, and instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…30 Blood Aβ has been measured using both ultrasensitive immunoassays 31,32 and mass spectrometry-based methods. 33,34 35,36 and increases more quickly than blood NfL and, after peaking, it rapidly decreases. Blood GFAP also increases in other neurodegenerative disease like AD, likely in response to Aβ pathology 23,32,37 and, particularly in frontotemporal dementia 20 due to progranulin (PGNR) mutations.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…30 Blood Aβ has been measured using both ultrasensitive immunoassays 31,32 and mass spectrometry-based methods. 33,34 35,36 and increases more quickly than blood NfL and, after peaking, it rapidly decreases. Blood GFAP also increases in other neurodegenerative disease like AD, likely in response to Aβ pathology 23,32,37 and, particularly in frontotemporal dementia 20 due to progranulin (PGNR) mutations.…”
Section: Introductionmentioning
confidence: 97%
“…This release results in a primary (hours) and secondary (days) peaks in which the latter is predictive of neurological outcome 30 . Blood Aβ has been measured using both ultrasensitive immunoassays 31,32 and mass spectrometry‐based methods 33,34 . These studies have shown that blood Aβ42 and/or the Aβ42/Aβ40 ratio correlates with those in the CSF and with Aβ PET and can discriminate Aβ‐positive individuals from those who are Aβ‐negative.…”
Section: Introductionmentioning
confidence: 99%
“…However the retention time of the sample is slightly slower than the standard. A comparison of the retention times is presented in Table 1 The time consumed for the present method in identifying  and  acids is better than the results where the retention time of alpha acid is above 10 minutes and  acids is greater than 19 minutes [20]. In addition, the samples were quite well separated indicating that some impurities appeared and separated by retention time on the range of 1.1 -4.5 minutes.…”
Section: Separation α and β-Acidsmentioning
confidence: 72%
“…This is due to the similarity of the hydrophobicity of humulone with adhumulone and lupulone with adlupulone. Only four chromatograms found, these are shown on Figure 1 [20]. The use of pH 2.8, which might reduce the variability in spacing and increase the resolution, considering that the two analytes have a pKa ranging from 4.25 to 5.93.…”
Section: Separation α and β-Acidsmentioning
confidence: 99%
See 1 more Smart Citation